PlGF Levels and Blood Pressure in Pregnant Women with Hypertension - Simanjuntak, Veronica; Runjati, Runjati; Suharsono, Suharsono; Arwani, Arwani (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Hypertension in pregnancy is one of the causes of morbidity and mortality in mothers and babies. PlGF has been shown to be associated with the diagnosis of hypertensive disorders in pregnancy. Pregnant women with hypertension are characterized by reduced circulating PlGF levels, even before clinical signs and symptoms. A decrease in the amount of PlGF is positively correlated with the severity of disease progression This study aimed to analyze the relationship between PlGF levels and blood pressure in pregnant women with hypertension. Observational analytic with cross sectional study design.  Sampling was total sampling. The number of subject were 34 peoples. The results showed that there was no significant correlation between PlGF levels and blood pressure in pregnant women with hypertension. PlGF levels have no relationship with blood pressure.